Mercury exposure driven by geographic and trophic factors in Magellanic penguins from Tierra del Fuego - Dodino, Samanta Graciela; Riccialdelli, Luciana; Polito, Michael J.; Pütz, Klemens; Brasso, Rebecka L.; Raya Rey, Andrea Nélida (Marine Pollution Bulletin)
Penguins accumulate mercury due to their long-life span together with their high trophic position. We sampled adult and juveniles' feathers from three colonies of Spheniscus magellanicus from Tierra del Fuego along an inshore-offshore corridor. We integrated toxicological information (mercury concentrations) and foraging biomarkers (δ13C, δ15N) into a common data analysis framework (isotopic niche analysis) to evaluate the influence of age, location, and foraging behaviors on mercury concentrations. Adults had higher feather mercury concentrations, δ13C, and δ15N values compared to juveniles. Also, adult and juvenile feather mercury concentrations differed between colonies, with lower mercury concentrations at the nearest inshore colony relative to the farther offshore colonies. Trophic position and the isotopic niche analyses suggest that this geographic gradient in mercury concentrations is due to differences in colonies' foraging areas. Understanding penguins' exposure to mercury derived from local food webs is a crucial first step in evaluating the impacts of this heavy metal on their conservation status. Fil: Dodino, Samanta Graciela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Riccialdelli, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Polito, Michael J. Louisiana State University; Estados Unidos Fil: Pütz, Klemens. Antarctic Research Trust; Estados Unidos Fil: Brasso, Rebecka L. Weber State University; Estados Unidos Fil: Raya Rey, Andrea Nélida. Wildlife Conservation Society; Estados Unidos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina